Social behavior in the “Age of Empathy”?—A social scientist's perspective on current trends in the behavioral sciences - Matusall, Svenja (Frontiers in Human Neuroscience, 2013)
Recently, several behavioral sciences became increasingly interested in investigating biological and evolutionary foundations of (human) social behavior. In this light, prosocial behavior is seen as a core element of human nature. A central role within this perspective plays the ‘social brain’ that is not only able to communicate with the environment but rather to interact directly with other brains via neuronal mind reading capacities such as empathy. From the perspective of a sociologist, this paper investigates what “social” means in contemporary behavioral and particularly brain sciences. It will be discussed what “social” means in the light of social neuroscience and a glance into the history of social psychology and the brain sciences will show that two thought traditions come together in social neuroscience, combining an individualistic and an evolutionary notion of the “social”. The paper concludes by situating current research on prosocial behavior in broader social discourses about sociality and society, suggesting that to naturalise prosocial aspects in human life is a current trend in today's behavioral sciences and beyond.